Detection of Methicillin Resistance in Staphylococcus aureus From Agar Cultures and Directly From Positive Blood Cultures Using MALDI-TOF Mass Spectrometry-Based Direct-on-Target Microdroplet Growth Assay - Nix, Ilka D.; Idelevich, Evgeny A.; Storck, Luise M.; Sparbier, Katrin; Drews, Oliver; Kostrzewa, Markus; Becker, Karsten (Frontiers in Microbiology, 2020)
MALDI-TOF mass spectrometry (MS)-based direct-on-target microdroplet growth assay (DOT-MGA) was recently described as a novel method of phenotypic antimicrobial susceptibility testing (AST). Here, we developed the application of MALDI-TOF MS-based DOT-MGA for Gram-positive bacteria including AST from agar cultures and directly from positive blood cultures (BCs) using the detection of methicillin resistance as example. Consecutively collected, a total of 14 methicillin-resistant S.aureus (MRSA) and 14 methicillin-susceptible S.aureus (MSSA) clinical isolates were included. Furthermore, a collection of MRSA challenge strains comprising different SCCmec types, mec genes and spa types was tested. Blood samples were spiked with MRSA and MSSA and positive BC broth processed by three different methods: serial dilution of BC broth, lysis/centrifugation and differential centrifugation. Processed BC broth was directly used for rapid AST using DOT-MGA. Droplets of six microliters with and without cefoxitin at the EUCAST breakpoint concentration were spotted in triplicates onto the surface of a MALDI target. Targets were incubated in a humidity chamber, followed by medium removal and on-target protein extraction with formic acid before adding matrix with an internal standard as a quality control. Spectra were acquired and evaluated using MALDI Biotyper software. First, tests were considered as valid, if the growth control achieved an identification score of ≥1.7. For valid tests, same score criterion was used for resistant isolates when incubated with cefoxitin. An identification score <1.7 after incubation with cefoxitin defined susceptible isolates. On-target protein extraction using formic acid considerably improved detection of methicillin resistance in S.aureus and DOT-MGA showed feasible results for AST from agar cultures after four hours incubation time. Comparing the different processing methods of positive BC broth, lysis/centrifugation method with a final dilution step 10-1 of the 0.5 McFarland suspension resulted in best test performance after four hours incubation time. Overall, 96.4% test validity, 100% sensitivity and 100% specificity were achieved for detection of methicillin resistance in clinical isolates. All strains of the MRSA challenge collection were successfully tested as methicillin-resistant. This first study on Gram-positive organisms showed feasibility and accuracy of MALDI-TOF MS-based DOT-MGA for rapid AST of S.aureus from agar cultures and directly from positive BCs.